Use of Fluconazole in Pulmonary Mycosis : A Case Report - Trowce Lista Nalle (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
The diagnostic criteria for pulmonary mycosis are long-term use of invasive medical devices, long-term use of broad-spectrum antibiotics and corticosteroids, lung infiltrate images with unfavorable fever after adequate antibiotic treatment, an increase in eosinophil count. Should be considered during patients undergoing hospitalization, from the beginning the antifungal that fluconazole can be used. Fluconazole is recommended for candida infections by the FDA because it is safe, fewer side effects and better tolerated than other antifungal classes.